SHIITAKE MUSHROOM AS A CAUSE OF BOWEL OBSTRUCTION - Chiew Yen, Felicia Kong; Palayan, Kandasami; Manohkaran, Subhathira (British Journal Of Surgical Science, 2021)
Shiitake mushroom, claimed to have major health benefits. It is a popular ingredient in east Asian cuisine. Given that mushrooms are rich in dietary fiber, the undigested fiber can act as a bezoar and may cause small bowel obstruction. Bezoar-induced small bowel obstructions are rare and herein we report a case of intestinal obstruction caused by shiitake mushroom. An elderly patient was admitted with features of intestinal obstruction. Preoperative imaging showed dilated small bowel with suspicious mass in ileum. Patient underwent laparotomy and undigested shiitake mushroom was retrieved at enterotomy. Clinical awareness of the mushroom induced intestinal obstruction and early use abdominal computed tomography (CT) are essential for prompt diagnosis and treatment.